2010
DOI: 10.1007/s10209-010-0212-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of previous exposure to technology on acceptance and its importance in usability and accessibility engineering

Abstract: In Usability and Accessibility Engineering, metric standards are vital. However, the development of a set of reciprocal metrics-which can serve as an extension of, and supplement to, current standards-becomes indispensable when the specific needs of end-user groups, such as the elderly and people with disabilities, are concerned. While ISO 9126 remains critical to the usability of a product, the needs of the elderly population are forcing the integration of other factors. Familiarity and recognisability are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 43 publications
6
54
1
2
Order By: Relevance
“…Nevertheless, it is important to consider that older adults have expressed their interest in using modern devices however, feel that modern technology is not suitably designed for their abilities (Goddard & Nicolle, 2012). Holzinger, Searle & Wernbacher (2011) described some usability metrics ascertained on the basis of experiments made with applications for elderly people throughout the summer term of 2007. The factors that influence the older users' acceptance of software, including the extent of their previous exposure to technology, were evaluated in order to provide short guidelines for software developers on how to design and develop software for the elderly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, it is important to consider that older adults have expressed their interest in using modern devices however, feel that modern technology is not suitably designed for their abilities (Goddard & Nicolle, 2012). Holzinger, Searle & Wernbacher (2011) described some usability metrics ascertained on the basis of experiments made with applications for elderly people throughout the summer term of 2007. The factors that influence the older users' acceptance of software, including the extent of their previous exposure to technology, were evaluated in order to provide short guidelines for software developers on how to design and develop software for the elderly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even if they had not any previous experience with them before, learning how to use them would be advantageous, since these devices will become useful in some moment of their lives. Besides, Holzinger et al [7] discussed the acceptance of technology and the tolerance of individuals to introduce a new device in their routine. A person with cognitive disability, yet having been trained in its use, will not use the device in his/her real life if there is no total acceptance of it.…”
Section: Introductionmentioning
confidence: 99%
“…However, interestingly users' subjective ratings suggest that they preferred the paper format (Holzinger, Searle, Wernbacher, 2011). This indicated that even when information displayed digitally is processed as effectively as information on a computer screen, non-computerized versions can still be preferred.…”
Section: Introductionmentioning
confidence: 99%